Dinosaur Footprints and Trackways of La Rioja - Perez Lorente, Felix (Book collections on Project MUSE., 2015)
During the Early Cretaceous, lakes, meandering streams, and flood plains covered the region where the current foothills of Rioja now exist. Today the area is known for its wine and for the dozens of sites where footprints and trackways of dinosaurs, amphibians, and even pterosaurs can be seen. The dinosaurs that lived here 120 million years ago left their footsteps imprinted in the mud and moist soil. Now fossilized in rock, they have turned Rioja into one of the most valuable dinosaur footprint sites in all of Europe. Felix Perez-Lorente and his colleagues have published extensively on the re.